Subsurface identification in the Surabaya and Waru segment areas using the Multichannel Analysis of Surface Waves (MASW) method - Gustono Sandy Tri; Sucipto Ari; Permana Dadang; Akbar Dzikrullah (E3S Web of Conferences, 2023)
Surabaya, especially the western part of Surabaya, has a diverse geological structure. As part of the Kendeng Zone, Surabaya has sedimentary rock formations that form anticlines and alluvium formations. In addition, the Kendeng Fault passes through Surabaya (Surabaya Segment and Waru Segment). This study aims to identify the structure of the soil to a depth of 30 meters using the Multichannel Analysis of Surface Waves (MASW) method which will be further processed into 2D slices with a North-South orientation. This research uses 11 field observation data from the Meteorology, Climatology, and Geophysics Agency in 2020 and 2023. The results of the 2D slices show that the range of Vs30 values is in the range of 92.8 m/s - 213.6 m/s and the Vs values for each depth layer are in the range of 88 m/s - 245 m/s. Based on SNI 1726:2019, both ranges indicate the classification of soft soil (SE) to medium soil (SD). The 2D section also shows a clear anticline on the section and the alleged Kendeng Fault.